Histological studies of diabetic foot samples obtained from patients treated with Argovit nanosilver; 2nd International Symposium on Nanoscience and Nanomaterials SINN, Ensenada, Baja California, Mexico, March 4-8, 2012, CNyN-UNAM, "Welcome to the Bionanotechnology Group" - Montes M. I. P.; Bogdanchikova N.; Rodarte D. V.; Vazquez R. M.; Ordaz M. A. V.; Onate Angulo G.; Aztorga C. A. O.; Albanez J. R. R.; Duarte A. C.; Ocampo G. J. F.; Burmistrov V.; Pestryakov A. N. Aleksey Nikolaevich; et al. (2013, 2013)
В фонде НТБ ТПУ отсутствует